Pimarane-derived diterpenoids with anti-Helicobacter pylori activity from the tuber of Icacina trichantha. Issue 12 (15th April 2021) - Xu, Ming-Ming; Zhou, Junfei; Zeng, Liping; Xu, Jingchen; Onakpa, Monday M.; Duan, Jin-Ao; Che, Chun-Tao; Bi, Hongkai; Zhao, Ming
Abstract : Two novel diterpenoids and ten known analogs were obtained from the tuber of Icacina trichantha . All compounds exhibited antibacterial activity against Helicobacter pylori strains with MIC values ranging from 8 to 64 μg mL −1 . Abstract : An unprecedented dimeric pimarane-derived diterpenoid (trichanthol A, 1 ) and a new 17- nor -(9β-H)-pimarane diterpenoid glucoside (trichanthol B, 2 ) together with ten known analogs (3–12 ) were obtained from the tuber of Icacina trichantha (Icacinaceae) in a bioassay-guided phytochemical investigation. Trichanthol A (1 ) is the first example of a pimarane-derived diterpenoid dimer furnished by forming an undescribed C-16–C-7′ linkage, and this is the first report of the glucosylation of a 17-nor-(9β-H)-pimarane diterpenoid (2 ). Their structures were elucidated by the interpretation of spectroscopic data and chemical methods in combination with calculated 13 C NMR-DP4+ analysis and electronic circular dichroism methods. All isolated compounds exhibited antibacterial activity against standard and drug-resistant Helicobacter pylori strains with MIC values ranging from 8 to 64 μg mL −1 . Moreover, icacinlactone B (6 ) showed an additive effect in combination with metronidazole or clarithromycin against H. pylori .